Lot-to-lot consistency, safety and immunogenicity of 3 lots of Haemophilus influenzae type b conjugate vaccine: results from a phase III randomized, multicenter study in infants. Issue 28 (16th June 2017) - Klein, Nicola P.; Abu-Elyazeed, Remon; Cornish, Matthew; Leonardi, Michael L.; Weiner, Leonard B.; Silas, Peter E.; Grogg, Stanley E.; Varman, Meera; Frenck, Robert W.; Cheuvart, Brigitte; Baine, Yaela; Miller, Jacqueline M.; et al.
Highlights: The study vaccine (Hib-TT) administered according to a 3 + 1 schedule is immunogenic. Immune responses to Hib-TT vaccination and to licensed Hib vaccines are comparable. Hib-TT primary and booster vaccination safety profiles are similar to other Hib vaccines. Immune response to routine vaccines is not impacted by co-administration with Hib-TT. Abstract: Background: Vaccination against Haemophilus influenzae type b (Hib) is included in routine pediatric immunization schedule in the United States. Previous vaccine shortages have created the need for additional options for Hib vaccination. Methods: This phase III, randomized, multi-centered study (NCT01000974 ) evaluated the safety and immunogenicity of a monovalent tetanus toxoid-conjugate Hib vaccine (Hib-TT) compared to a monovalent (Hib-TT control) and a combination Hib-TT vaccine. We hierarchically assessed lot-to-lot consistency of 3 Hib-TT lots and non-inferiority of Hib-TT to Hib-TT control. We co-administered routine pediatric vaccines with Hib-TT vaccines at 2, 4, 6 months (primary vaccination) and 15–18 months of age (booster vaccination). We recorded adverse events (AEs) for 4 (solicited) and 31 days (unsolicited) post-vaccination and serious AEs (SAEs) throughout the study. Results: Of 4009 enrolled children, 3086 completed booster phase. Lot-to-lot consistency was not demonstrated. The study met statistical criteria for non-inferiority of Hib-TT to Hib-TT control in terms of immune responses to Hib and co-administered vaccines' antigens, but not in terms of participants achieving post-primary vaccination anti-PRP levels ≥1 µg/mL. Because of the hierarchical nature of the objectives, non-inferiority could not be established. In all groups, 92.5–96.7% and 99.6–100% of participants achieved anti-PRP levels ≥0.15 µg/mL, while 78.3–89.8% and 97.9–99.1% had anti-PRP levels ≥1 µg/mL, post-primary and post-booster vaccination, respectively. Immune responses to co-administered vaccines and reported incidence of AEs were comparable among groups. We recorded SAEs for 107/2963 (3.6%), 24/520 (4.6%), and 21/520 (4.0%) children post-primary vaccination, and 29/2337 (1.2%), 4/435 (0.9%), and 2/400 (0.5%) children post-booster vaccination with Hib-TT, Hib-TT control and combination Hib-TT vaccine, respectively; 6/5330 (0.1%) SAEs in the Hib-TT groups were considered vaccine-related. Conclusion: Hib-TT induced seroprotective antibody concentrations in the majority of participants and was well-tolerated when co-administered with routine pediatric vaccines according to a 3 + 1 schedule.